The Relationship Between Future Orientation, Motivational Support, Learning Environment, Technological Accuracy and Learning Outcomes of Players: Evidence from Sports Clubs in China - Wan, Yuehong (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The objective of this study is to examine the relationship between future orientation, motivational support, learning environment, technological accuracy and learning outcomes. In this direction, the direct effect of future orientation, motivational support and learning environment was examined on learning outcomes of players. The moderating role of technological accuracy was also examined. The primary data were utilized in this study to examine this relationship. Therefore, a survey instrument was used for data collection. Respondents of the study was the players from various sports clubs in China. A statistical tool, namely; Partial Least Square (PLS) was used for data analysis. PLS measurement model and structural model was used in the data analysis process. Results of the data analysis demonstrated that; future orientation has positive effect on learning outcomes of players. Motivational support also has positive effect on learning outcomes. Similarly, technological orientation also has positive effect on learning outcomes. However, learning environment has no effect on learning outcomes. Finally, this study has important insights for the sports club management to enhance the players learning.